Efektivitas Shadow Training terhadap Kemampuan Smash Bola Voli pada Peserta Ekstrakurikuler Mts Islamiyah Temayang - Muhammad Nurudin Afila; Hasan Saifuddin; Hilmy Aliriad (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to analyze the effectiveness of shadow training on volleyball smash ability among extracurricular participants at MTs Islamiyah Temayang. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The research subjects consisted of 19 male students selected through purposive sampling. The research instrument was a volleyball smash ability test that had established validity and reliability. The research procedure included a pretest, the implementation of shadow training over several sessions, and a posttest. Data analysis techniques involved descriptive statistics, the Shapiro-Wilk normality test, and hypothesis testing using a paired sample t-test assisted by SPSS version 30. The results showed an improvement in smash ability after the implementation of shadow training, as indicated by an increase in the mean score from 8.95 to 12.42. The normality test results indicated that the data were normally distributed (Sig. > 0.05), thus meeting the assumptions for parametric testing, while the paired sample t-test results showed a significance value of < 0.001 (p < 0.05) with a t-value of -6.979, indicating a significant difference between the pretest and posttest results. These findings demonstrate that shadow training is effective as an alternative training method in improving volleyball smash ability through enhancing movement coordination, timing, and structured technical mastery, although the improvement was not evenly distributed among all participants. Therefore, this study provides practical contributions for coaches and physical education teachers in developing effective training models that align with the characteristics of madrasah-level students.